Samoa : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The impact of the 2009 tsunami on tourism and on the Samoan economy is likely to be substantial. The effectiveness of monetary transmission in Samoa has improved over time; however, it is still below international standards. The adverse impact of the crisis on the functioning of the banking system may be alleviated by an improvement in the financial infrastructure. State-owned enterprises (SOE) continue to play an important role in Samoa, and the key to successful SOE reform in Samoa will be placing them on a fully commercial footing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet